The sustainable homestead : create a thriving permaculture ecosystem with your garden, animals, and land - Ferraro-Fanning, Angela (Cool Springs Press, 2023)
"Live the dream and make the most of your land by working with it, not against it. From capturing water and building strong soil to helping your animals live their best lives, this book is all about making your homestead stronger by achieving synergy between its different parts." -- Back cover.